The combination of hprt and gapdh is the best compound reference genes in the fetal rat hippocampus. Issue 7 (26th October 2020) - Jiang, Tao; Dai, Shiyun; Yi, Yiwen; Liu, Yi; Zhang, Shuai; Luo, Mingcui; Wang, Hui; Xu, Dan
Abstract: Hippocampus, as an important organ of central memory storage and spatial orientation, has been studied increasingly in recent years. The expression of reference genes in the hippocampus of adult rats, which are commonly used in the quantitative real‐time polymerase chain reaction (qRT‐PCR), is unstable in the fetal hippocampus and may not be suitable for the fetal period. Therefore, this study intends to screen and determine the optimal compound reference genes in the fetal rat hippocampus. Based on the literature, we selected five housekeeping genes (HKGs), including glyceraldehyde 3‐phosphate dehydrogenase (gapdh), actin beta (β‐actin), hypoxanthine phosphoribosyltransferase (hprt), 18s ribosomal RNA (18s rRNA), and cyclophilin B (cypB). We analyzed the expression of them under physiological conditions in the fetal rat hippocampus using BestKeeper, GeNorm, and NormFinder, to select the most stable compound reference genes. Furthermore, to verify the stability of the compound reference genes, we analyzed the expression of reference genes in the fetal rat hippocampus under the pathological model of prenatal dexamethasone exposure (PDE). Finally, we evaluated the accuracy of compound reference genes through detecting the expression of fetal rat hippocampal brain‐derived neurotrophic factor (BDNF) under PDE model. This study determined that the combination of gapdh and hprt was the most stable and suitable compound reference genes in the fetal rat hippocampus. There was no significant difference between male and female fetal rats. We provided the support of accurate and reliable reference genes for the further study of diseases related to the fetal hippocampus.